PRAWO I ETYKA W MEDYCYNIELegal aspects of promoting medicaments - Wroński, Konrad (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
At the present time pharmaceutical companies are among the largest firms in the global economy. Their main objective is to make maximum profits, which is why the promotion of their products by sales representatives is extremely aggressive. Doctors coming in contact with sales representatives should be familiar with legal aspects of promoting pharmaceutical products. This article presents legal aspects of promoting medicaments.